The importance of financial literacy among degree students: a case study in UiTM Kedah campus / Dahlia Ibrahim, Rabitah Harun, Zuraidah Mohamed Isa - Ibrahim, Dahlia; Harun, Rabitah; Mohamed Isa, Zuraidah (Institute of Research Management & Innovation (IRMI), 2009)
Interest in exploring the issues of personal finance, particularly money management, has tremendously increased in recent years due to the society’s awareness on its importance. This research attempts to explore the development, issues and concerns of the present financial literacy level among degree students in UiTM Kedah campus. Money management skill is a vital element in disciplining them to achieve a quality life as working adults because students spending habits in campus will influence the way they manage money throughout their lives. Looking at the previous literatures from researches outside of Malaysia reveals that financial literacy among students is needed to curb any future problems that may arise due to lack of knowledge on individual financial management. This research stresses on the importance of financial literacy among students, targeting at degree students in UiTM Kedah by looking into the student’s background, financial attitude, financial knowledge and family. The data obtained from questionnaires and secondary data were analysed using SPSS version 12.0. From the data analysis, majority of students do not practice proper money management skills. Hence, researchers hope there will be measures taken to step aside this scenario. The recommendation and limitation were also included to assist those future researches who are interested to study further on this topic.